Pemetaan dan Evaluasi Risiko Kebisingan di Area Produksi Menggunakan Golden Surfer - Ibrahim, Muchammad Sultan; Satoto, Handy Febri (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to map and evaluate noise levels in the production area of CV. Cipta Karya. Measurements were carried out using a Sound Level Meter at points determined by the grid lines method. The LAeq data were processed and visualized using Golden Surfer to produce a noise contour map. Several points in the Sawmill and Moulding areas exceeded the permissible limit (85 dB). The contour mapping provides a spatial overview useful for formulating noise control recommendations